Chapter 9 Relational Agency and the Local Governance of Climate Change International Trends and an American Exemplar - Aylett, Alexander (Cities and Global Governance, 2015)
Drawing upon a variety of empirical and theoretical perspectives, The Urban Climate Challenge provides a hands-on perspective about the political and technical challenges now facing cities and transnational urban networks in the global climate regime. Bringing together experts working in the fields of global environmental governance, urban sustainability and climate change, this volume explores the ways in which cities, transnational urban networks and global policy institutions are repositioning themselves in relation to this changing global policy environment. Focusing on both Northern and Southern experience across the globe, three questions that have strong bearing on the ways in which we understand and assess the changing relationship between cities and global climate system are examined. The Urban Climate Challenge will be of interest to scholars of urban climate policy, global environmental governance and climate change. It will be of interest to readers more generally interested in the ways in which cities are now addressing the inter-related challenges of sustainable urban growth and global climate change. Chapter 9 and Chapter 11 of this book are freely available as downloadable Open Access PDFs under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license. https://s3-us-west-2.amazonaws.com/tandfbis/rt-files/docs/Open+Access+Chapters/9781138776883_oachapter11.pdf Chapter 9 and Chapter 11 of this book are freely available as downloadable Open Access PDFs under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license. https://s3-us-west-2.amazonaws.com/tandfbis/rt-files/docs/Open+Access+Chapters/9781138776883_oachapter9.pdf